Veneer and Thin Plywood Overlaid for Quality Improvement of Particleboard Made of Palm Oil Empty Fruit Bunches (EFB) - Bambang Subiyanto; Entang Rasyid; Mohamad Gopar; Anita Firmanti (Jurnal Ilmu dan Teknologi Kayu Tropis, 2008)
Many efforts to find alternatives raw materials in the particleboards have been done and one of them is utilizing Empty Fruit Brunches (EFB) from palm oil production. Based on some reports, low performance of particleboards especially mechanical properties was obtained when using EFB as raw materials. Overlaying the particleboards made of EFB with veneer and thin plywood is predicted as one way to improve the quality of such particleboards. The raw material of overlaid particleboards was EFB, veneer of 2 mm Falcata, and 3 mm commercial plywood. Commercial urea formaldehyde (UF) and phenol formaldehyde (PF) were used as binder. The adhesive content varied from 8%, 10% to 12% based on oven dry of particles.  The size of board was 250 X 250 X 10 mm with target density of 0.6 g/cm3.The experiment results showed that particleboards made of EFB with UF resin demonstrated better physical and mechanical properties than particleboards with PF resin. It was also found that direct overlaying veneer and thin plywood on the surface of particleboards would significantly improve the   mechanical properties of the boards especially the modulus of elasticity and modulus of rupture.